2005
DOI: 10.1021/ct049881g
|View full text |Cite
|
Sign up to set email alerts
|

A Molecular Dynamics Simulation of the Binding Modes of d-Glutamate and d-Glutamine to Glutamate Racemase

Abstract: Classical molecular dynamics simulations of the d-Gln/Aquifex pyrophilus MurI and d-Glu/Aquifex pyrophilus MurI complexes have been carried out. Since the active site of the enzyme contains many charged and polar residues, several binding modes are possible. Thus, three very different stable conformations of the substrate analogue d-Gln have been found, and at least three binding modes are possible for the substrate d-Glu. These qualitative results give an explanation for the apparent disagreement between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 35 publications
0
22
0
Order By: Relevance
“…A solution of LLAziDAP (1-5 mg͞ml) was added in excess (10-100 eq) to a solution of DAP epimerase (0.54 mg͞ml) in a buffered solution (100 mM Tris⅐HCl͞1 mM EDTA͞1 mM DTT, pH 7.8) and incubated at room temperature for 16 h. To ensure complete inhibition, DAP epimerase activity was monitored spectrophotometrically by using a coupled assay with DAP dehydrogenase that detects the production of NADPH at 340 nm. An aliquot was removed and purified by RP-HPLC using a Jupiter (Torrance, CA) reverse-phase C 18 column. The purified enzyme was then dialyzed against Hepes buffer (pH 8.0, 25 mM Hepes͞5 mM DTT) and concentrated by using a Millipore Ultrafree Biomax 10K concentrator to a concen- …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A solution of LLAziDAP (1-5 mg͞ml) was added in excess (10-100 eq) to a solution of DAP epimerase (0.54 mg͞ml) in a buffered solution (100 mM Tris⅐HCl͞1 mM EDTA͞1 mM DTT, pH 7.8) and incubated at room temperature for 16 h. To ensure complete inhibition, DAP epimerase activity was monitored spectrophotometrically by using a coupled assay with DAP dehydrogenase that detects the production of NADPH at 340 nm. An aliquot was removed and purified by RP-HPLC using a Jupiter (Torrance, CA) reverse-phase C 18 column. The purified enzyme was then dialyzed against Hepes buffer (pH 8.0, 25 mM Hepes͞5 mM DTT) and concentrated by using a Millipore Ultrafree Biomax 10K concentrator to a concen- …”
Section: Methodsmentioning
confidence: 99%
“…The x-ray crystal structure of glutamate racemase has been reported with the substrate analogue D-glutamine (3), but the lack of any strong interactions with the enzyme allows for a variety of possible binding modes in molecular modeling studies and precludes convincing mechanistic deductions (18). Recently, Rice and coworkers (19) have reported that the crystal structure of D-glutamate bound to glutamate racemase from Bacillus subtilis; this structure revealed a ''closed conformation'' for this enzyme upon ligand binding.…”
mentioning
confidence: 99%
“…Two possibilities, which differ in the protonation states of the catalytic bases prior to the initial deprotonation, have been proposed (Glavas & Tanner, 2001; Ruzheinikov et al , 2005). Furthermore, stereochemistry, substrate ligation and active‐site protonation states have been investigated by molecular dynamics simulations (Möbitz & Bruice, 2004; Puig et al , 2005). Recently, the results from computational simulations on a quantum mechanical/molecular mechanical potential energy surface (Puig et al , 2006) indicated two possible roles for MurI as a catalyst and supported the mechanistic proposal by Rios et al (2000) for the PLP‐independent amino acid racemases.…”
Section: Side Pathwaysmentioning
confidence: 99%
“…These features, along with similar strong hydrogen‐bonding networks at the substrate amino group, have been rationalized in the context of the difficult and remarkable chemical transformations performed by the enzyme given the solution state pKa values of cysteine (pKa ∼ 10) and the α‐carbon of glutamate (fully protonated form, pKa ∼ 21). Computational and physical chemistry measurements suggest the hydrophobic environment, the hydrogen‐bonding networks to form and stabilize the amino‐protonated, main chain cationic form of substrate, and the soft ionization energy of the thiolate base work in concert to minimize both the penalty of desolvation of the substrate upon binding and the large pKa differential between the substrate and enzyme at the transition state (Rios et al ., 2000; 2001; 2002; Puig et al ., 2005; 2006; 2007). Additional studies have implicated dynamics as a key element in overcoming the activation barrier for catalysis (Möbitz and Bruice, 2004).…”
Section: Biochemical and Structural Characterizationmentioning
confidence: 99%